2015
DOI: 10.1007/s00292-014-2063-3
|View full text |Cite
|
Sign up to set email alerts
|

Aktinische Keratose, Morbus Bowen, Keratoakanthom und Plattenepithelkarzinom der Haut

Abstract: Actinic (solar) keratosis is an intraepidermal squamous neoplasm of sun-damaged skin and by far the most frequent neoplastic skin lesion. A subdivison into three grades has been proposed with increasing acceptance not least because of the therapeutic consequences. The transition to invasive squamous cell carcinoma is reported in 5-10 % and with immunosuppression in 30 % of patients.Bowen's disease is a variant of squamous cell carcinoma in situ of the skin and the mucocutaneous junction. The differentiation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…AK is an intra-epidermal keratinocyte-derived precancerous lesion in humans. BD is a variant of SCC in the skin and the mucocutaneous junction ( 20 ). The findings of the present study suggested that increased levels of AQP3 were correlated with proliferation in SCC, and with tumor progression from a precancerous lesion to a cancerous lesion in situ , and then to an invasive lesion.…”
Section: Discussionmentioning
confidence: 99%
“…AK is an intra-epidermal keratinocyte-derived precancerous lesion in humans. BD is a variant of SCC in the skin and the mucocutaneous junction ( 20 ). The findings of the present study suggested that increased levels of AQP3 were correlated with proliferation in SCC, and with tumor progression from a precancerous lesion to a cancerous lesion in situ , and then to an invasive lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these SCCs were well differentiated and keratinizing (KSCCs), containing high amounts of extrachromosomal and transcriptionally active MnPV genomes as observed previously in spontaneous MnPV-induced tumors ( Amtmann et al, 1984 ; Vinzón et al, 2014 ), whereas poorly differentiated and non-keratinizing SCCs (nKSCCs) only contained low amounts or even lacked viral DNA. Histologically KSCCs were similar to human AKs and Bowen’s disease ( Majores and Bierhoff, 2015 ) which also contain high viral loads whereas SCCs usually lack HPV DNA ( Weissenborn et al, 2005 ). However, irrespective of the tumor type, all tumor-bearing animals developed antibody responses against the viral L1 capsid protein, providing evidence for preceding infections, which again is seen in SCC patients ( Andersson et al, 2008 ).…”
Section: How Do the Current Rodent Models For Cutaneous Hpvs Fit To Tmentioning
confidence: 97%